Influence of the Combined Oral and Injectable Contraceptives on the Level of Creatinine, Urea, and Some Electrolyte - Haider Mahmooed Jasim (Journal of Global Pharma Technology, 2019)
This study was conducted to investigate the effect of combined oral contraceptives and injectable contraceptives on the Urea, Creatinine, Sodium and Potassium level. The study included 40 women used hormonal contraceptives who attending the family center of planning at the feminine and children hospital in Al- Muthanna Governorate. They were divided into two groups (combined oral contraceptives group and injectable contraceptives group) and were compared with control group (20 women do not use of contraceptives). The blood samples were collected to determine of serum Urea, Creatinine, Sodium and Potassium level. The results showed no significant differences in the level of Urea, Sodium and Potassium between the three study groups, while Creatinine showed a significant increase (0.01) in combined oral contraceptives group compared with injectable contraceptives and control groups. In conclusion, combined oral contraceptives and injectable contraceptives did not affect the level of Urea, Sodium and Potassium, except Creatinine, showed significant increase in women who used Compound oral contraceptives group.Keywords: Combined oral contraceptives, Injectable contraceptives, Serum electrolytes, Urea, Creatinine.